Partisipasi Hotel Menyajikan Makanan Tradisional Untuk Memperkenalkan Kuliner Yogyakarta - Heni Widyaningsih (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2013)
Yogyakarta is one area that has great potential in tourism. One type is a rapidly growing travel culinary tour. Trends tourists now come to a tourist area to search or hunt for traditional food typical of the area he visited. Restaurant which is the object of this study is the hotel's restaurants in the area joined in JCJHA DIY. Traditional foods commonly consumed by a particular community, with distinctive flavor that is accepted by the society. Results from observations and interviews conducted, all hotels in Yogyakarta joined in JCJHA have an active participation of the traditional food of Yogyakarta.  Keywords: Participation, Hotel, Traditional foods